DESIGN OF ENTERPRISE ARCHITECTURE FOR SMARTVILLAGE IN SUMUR BANDUNG SUB-DISTRICT (CASE STUDY: GOVERNANCE DIMENSION) - Dzaki Rachmanda Malik Imanudin; Berlian Maulidya Izzati; Fitriyana Dewi (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2022)
Smart village is one that is innovative in its use of information technology to improve quality of life, efficiency, and competitiveness in economic, social, and environmental aspects. Sumur Bandung sub-district can implement the smart village concept to intelligently solve their problems. Sumur Bandung sub-district is one of 30 sub-districts in the city of Bandung. Sumur Bandung sub-district has a Government Section which functions to carry out government duties in the sub-district. One of his duties is to be responsible for population administration services. For population administration services in Sumur Bandung sub-district still use a manual system that requires people to come to the sub-district to carry out population administration. As a result, it is necessary to implement a smart village in governance dimension that includes redesigning business processes for population administration services to use the latest information systems and technology. The use of this technology also needs to be aligned with the plan and strategy of Sumur Bandung sub-district. Enterprise architecture is a tool used to synchronize business needs with technology needs. Its design requires the TOGAF ADM 9.2 framework, which is used as a guide while creating enterprise architecture. The research method used is literature study. The results of this study are artifacts as general architecture. These results are expected to be useful and beneficial for Sumur Bandung sub-district, especially in the population administration service section, or become a reference for other researchers as well as insight for readers.